2018
DOI: 10.3390/genes9010046
|View full text |Cite
|
Sign up to set email alerts
|

The IFNG rs1861494 Single Nucleotide Polymorphism Is Associated with Protection against Tuberculosis Disease in Argentina

Abstract: Interferon gamma (IFNG) plays a key role during Mycobacterium tuberculosis (Mtb) infection, and several polymorphisms located in its gene are associated with risk of tuberculosis in diverse populations. Nevertheless, the genetic resistance/susceptibility to tuberculosis in Argentina is unknown. The IFNG rs1861494 polymorphism (G→A) was reported to alter the binding of transcription factors to this region, influencing IFNG production. Using a case-control study, we found an association between the AA and AG gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…The initial immunofluorescence identification of islet cell antibodies (ICA) in 1974 [66, 67] was a key step in recognizing type 1 diabetes as an immune-mediated disease. The ICA can identify any antibody that binds to human islet tissues in a nonspecific manner with immunofluorescent techniques [66, 67]. However, the ICA assay is difficult to standardize because it is operator-dependent, varies according to the quality of the human pancreatic tissue used as a substrate, and recognizes heterogeneous antibodies that vary among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The initial immunofluorescence identification of islet cell antibodies (ICA) in 1974 [66, 67] was a key step in recognizing type 1 diabetes as an immune-mediated disease. The ICA can identify any antibody that binds to human islet tissues in a nonspecific manner with immunofluorescent techniques [66, 67]. However, the ICA assay is difficult to standardize because it is operator-dependent, varies according to the quality of the human pancreatic tissue used as a substrate, and recognizes heterogeneous antibodies that vary among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the association between rs1861494 polymorphism and tuberculosis, but the results were inconsistent. A study from Argentina showed that rs1861494 polymorphism was associated with tuberculosis resistance in a dominant model [34]. Also, another study demonstrated that GG genotype was related to tuberculosis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, patients with tuberculosis (TB) displaying the most severe expression of the disease produce the lowest amounts of IFNG against the pathogen (5, 6). Moreover, we have reported that the IFNG rs1861494 single nucleotide polymorphism (SNP) would act as a biomarker of resistance to tuberculosis in the Argentinean population, since it affects the secretion of IFNG (7). However, other cytokines might be participating in the fight of the host against Mtb infection, given that only IFNG is not enough to completely eliminate the bacteria (8).…”
Section: Introductionmentioning
confidence: 99%